2022
DOI: 10.31305/rrijm.2022.v07.i01.012
|View full text |Cite
|
Sign up to set email alerts
|

The M-polynomials of some Chemical Graphs

Abstract: The chemical graph theory (CGT)is one of the branches in mathematical chemistry. It is utilized to address the number of problems related to molecular theory which has its utilization in graph theory as an application. The CGT reduces the structure of the molecule to a single value which is used to mark either to its structural fragments, orbital’s, the molecular branching, energy of the molecule as a whole, its electronic structures and many other properties by using these invariants. These invariants estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In [11], the 𝑀-polynomial of the two-dimensional three-layered single-walled titania nanotube lattice was studied by Raheem et al, The topological indices through M-polynomial of book graphs were found by Khalaf et al, [12]. Some other works related to Mpolynomials was also found in [13,14]. In this paper, we compute the topological indices of Boron Kagome Lattice with the help of M-polynomial.…”
Section: 𝑠𝑙∈𝐸(𝐺)mentioning
confidence: 90%
“…In [11], the 𝑀-polynomial of the two-dimensional three-layered single-walled titania nanotube lattice was studied by Raheem et al, The topological indices through M-polynomial of book graphs were found by Khalaf et al, [12]. Some other works related to Mpolynomials was also found in [13,14]. In this paper, we compute the topological indices of Boron Kagome Lattice with the help of M-polynomial.…”
Section: 𝑠𝑙∈𝐸(𝐺)mentioning
confidence: 90%